1986
DOI: 10.3354/meps034197
|View full text |Cite
|
Sign up to set email alerts
|

A new theory to explain the origin of growth lines in sea urchin spines

Abstract: A new theory IS proposed to explain the origln of some growth lines in echinoid splnes. It is proposed that lines form as part of a growth event initiated when a usually nongrowing spine no longer fits the growing tubercle on which it sits. Growth lines also can form in response to damage but neither cause of growth lines is periodic and hence lines cannot be used to determine age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…(), although the overall effect is to create conical layers, the calcification appears to occur in a patchwork with migrating cells laying down areas of calcite. Ultimately, the aggregate calcification leads to spine growth lines (Deutler ) that are not entirely age‐ or size‐dependent (Ebert , ) and to a structure with magnesium concentrations toward the outer edge of spines that strengthen the load‐bearing columns in the spines (Tsafnat et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…(), although the overall effect is to create conical layers, the calcification appears to occur in a patchwork with migrating cells laying down areas of calcite. Ultimately, the aggregate calcification leads to spine growth lines (Deutler ) that are not entirely age‐ or size‐dependent (Ebert , ) and to a structure with magnesium concentrations toward the outer edge of spines that strengthen the load‐bearing columns in the spines (Tsafnat et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In this hypothesis, growth of the spine would be triggered to maintain the correct allometric relations between spines and the continuously growing test. As stressed by Ebert (1986) himself, this hypothesis is only valid if spines are not continuously growing. However, Heatfield (1971b) showed a significant incorporation of 3 H-thymidine in intact spines, an observation that questions Ebert's hypothesis.…”
Section: Spine Regenerationmentioning
confidence: 99%
“…The periodic nature vs. the traumatic origin of these rings was much debated. It is now considered that spine rings do not have a periodic origin (and thus cannot be used to age sea urchins) (Ebert, 1986). According to Ebert, they would originate from either a trauma and subsequent regeneration, as explained above, or from an endogenous signal triggered by the tension developing between the base of the nongrowing spine and the continuously growing tubercle (or mam-melon) on which it sits.…”
Section: Spine Regenerationmentioning
confidence: 99%
“…The calcite spines covering the test of the sea urchin 129 serve as the primary interface with the environment and predators (Strathman, 1981), and aid in 130 movement (Hyman, 1955), and therefore their repair is important. While the process of spine 131 regeneration has been well established (Ebert, 1967(Ebert, , 1968(Ebert, , 1984(Ebert, , 1986(Ebert, , 19881991), there is 132 some debate as to whether this regeneration is independent of test and reproductive growth. 133 Kawakami (1998) found that a poor quality diet can lead to spine shedding, suggesting a link 134 between nutrition and spine maintenance.…”
Section: Introduction 63mentioning
confidence: 99%